Household environmental characteristics influence the house dust metagenome - Isabella Gamez; Farnaz Fouladi; Antonio Gonzalez; James Ward; Ziyue Wang; Laura E. Beane Freeman; Alison Motsinger-Reif; Shyamal D. Peddada; Rob Knight; Mikyeong Lee; Stephanie J. London (Environmental Research, 2026)

Environmentally relevant concentrations of a Bacillus thuringiensis-based biopesticide impair zebrafish behavior - Stephanie Toussaint; Aline Pompermaier; Flavia Bernardo Chagas; Wagner Antonio Tamagno; Jennifer L. Freeman; Paulo Afonso Hartmann; Marilia Hartmann (Aquatic Ecology, 2025)

Animal farming and the oral microbiome in the Agricultural Health Study - Vicky C. Chang; Vaishnavi Purandare; Shilan Li; Gabriella Andreotti; Xing Hua; Yunhu Wan; Casey L. Dagnall; Kristine Jones; Belynda D. Hicks; Amy Hutchinson; Yukiko Yano; Kathryn R. Dalton; et al. (Environmental Research, 2025)

A Shoreline Screening Framework for Identifying Nature-Based Stabilization Measures Reducing Storm Damage in the Florida Keys - Diana Mitsova; Kevin Cresswell; Chris Bergh; Melina Matos; Stephanie Wakefield; Kathleen Freeman; Willian Carlos Lima (Journal of Marine Science and Engineering, 2025)
With elevations mostly less than 2 m, the Florida Keys, an island chain stretching nearly two hundred kilometers from Biscayne Bay to Key West, Florida, is among the most vulnerable coastal regions globally. As the threats from tropical cyclones, storm surges, and sea level rise intensify, urbanized areas increasingly rely on shoreline armoring, disregarding the negative effects on coastal habitats. Living shorelines, which integrate coastal vegetation to stabilize erodible shoreline segments or enhance existing grey infrastructure, have successfully addressed some of these challenges. We present a decision framework for evaluating the suitability of different stabilization methods for existing shoreline conditions. The framework incorporates a Shoreline Relative Exposure Index (SREI) based on shoreline orientation, wind and wave exposure, shoreline slope, bathymetry, nearshore habitat, and storm surge. To refine this framework, we conducted an expert opinion survey to determine parameter weights. The results will inform decisions on using vegetated shorelines alone or with structural elements to reduce wave action, control erosion, and protect Florida Keys communities from storm damage. Implementing innovative shoreline stabilization methods is crucial as climate change and population growth are expected to exacerbate flood management challenges.

Occupational farm work activities influence workers’ indoor home microbiome - Kathryn R. Dalton; Mikyeong Lee; Ziyue Wang; Shanshan Zhao; Christine G. Parks; Laura E. Beane-Freeman; Alison A. Motsinger-Reif; Stephanie J. London (Environmental Research, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Development of a Seafloor Community Classification for the New Zealand Region Using a Gradient Forest Approach - Fabrice Stephenson; Ashley A. Rowden; Tom Brough; Grady Petersen; Richard H. Bulmer; John R. Leathwick; Andrew M. Lohrer; Joanne I. Ellis; David A. Bowden; Shane W. Geange; Greig A. Funnell; Debbie J. Freeman; et al. (Frontiers in Marine Science, 2022)
To support ongoing marine spatial planning in New Zealand, a numerical environmental classification using Gradient Forest models was developed using a broad suite of biotic and high-resolution environmental predictor variables. Gradient Forest modeling uses species distribution data to control the selection, weighting and transformation of environmental predictors to maximise their correlation with species compositional turnover. A total of 630,997 records (39,766 unique locations) of 1,716 taxa living on or near the seafloor were used to inform the transformation of 20 gridded environmental variables to represent spatial patterns of compositional turnover in four biotic groups and the overall seafloor community. Compositional turnover of the overall community was classified using a hierarchical procedure to define groups at different levels of classification detail. The 75-group level classification was assessed as representing the highest number of groups that captured the majority of the variation across the New Zealand marine environment. We refer to this classification as the New Zealand “Seafloor Community Classification” (SCC). Associated uncertainty estimates of compositional turnover for each of the biotic groups and overall community were also produced, and an added measure of uncertainty – coverage of the environmental space – was developed to further highlight geographic areas where predictions may be less certain owing to low sampling effort. Environmental differences among the deep-water New Zealand SCC groups were relatively muted, but greater environmental differences were evident among groups at intermediate depths in line with well-defined oceanographic patterns observed in New Zealand’s oceans. Environmental differences became even more pronounced at shallow depths, where variation in more localised environmental conditions such as productivity, seafloor topography, seabed disturbance and tidal currents were important differentiating factors. Environmental similarities in New Zealand SCC groups were mirrored by their biological compositions. The New Zealand SCC is a significant advance on previous numerical classifications and includes a substantially wider range of biological and environmental data than has been attempted previously. The classification is critically appraised and considerations for use in spatial management are discussed.

Mutualism Wildlife Value Orientations Predict Support for Messages About Distance-Related Wildlife Conflict - Stephanie Freeman; B. Derrick Taff; Zachary D. Miller; Jacob A. Benfield; Peter Newman (Environmental Management, 2021)

Role of DNA methylation in the dietary restriction mediated cellular memory - Archana Unnikrishnan; Jordan Jackson; Stephanie A. Matyi; Niran Hadad; Benjamin Wronowski; Constantin Georgescu; Karla P. Garrett; Jonathan D. Wren; Willard M. Freeman; Arlan Richardson (GeroScience, 2017)

Proceedings of the third international molecular pathological epidemiology (MPE) meeting - Peter T. Campbell; Timothy R. Rebbeck; Reiko Nishihara; Andrew H. Beck; Colin B. Begg; Alexei A. Bogdanov; Yin Cao; Helen G. Coleman; Gordon J. Freeman; Yujing J. Heng; Curtis Huttenhower; Rafael A. Irizarry; et al. (Cancer Causes & Control, 2017)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

Maternal age and risk for trisomy 21 assessed by the origin of chromosome nondisjunction: a report from the Atlanta and National Down Syndrome Projects - Emily Graves Allen; Sallie B. Freeman; Charlotte Druschel; Charlotte A. Hobbs; Leslie A. O’Leary; Paul A. Romitti; Marjorie H. Royle; Claudine P. Torfs; Stephanie L. Sherman (Human Genetics, 2009)

Molecular characterization of mesophilic and thermophilic sulfate reducing microbial communities in expanded granular sludge bed (EGSB) reactors - Stephanie A. Freeman; Reyes Sierra-Alvarez; Mahmut Altinbas; Jeremy Hollingsworth; Alfons J. M. Stams; Hauke Smidt (Biodegradation, 2008)